Estimation of genetic parameters for dairy traits using repeatability animal models based on test-day data for Alpine goat in Croatia - Špehar, Marija (Array, 2019)
The objective of this study was to estimate genetic parameters for daily milk yield (DMY), fat (FC), and protein content (PC) using 329.022 test-day records of 23.756 Alpine does. Single trait repeatability animal model was applied. Parity, litter size, season, and lactation stage (Ali-Schaeffer’s curve) were fitted in the fixed, while herd, herd-test-day, permanent environment (within lactations) and additive genetic effect in the random part of the model. Variance components were estimated using Residual Maximum Likelihood Method in the VCE-6 program. Additive genetic effect explained 23 %, 16 % and 25 % of DMY, FC and PC variability which is in general agreement with numerous previous reports for dairy goat breeds. Among the non-genetic effects, herd explained 24 %, 12 %, and 9 %, herd-test-day 17 %, 29 %, and 30 %, and permanent environment 16 %, 3 %, and 5 % of DMY, FC and PC variability, respectively. The estimated parameters and developed single trait repeatability test-day models will serve as a basic tool in BLUP based genetic evaluation of Alpine breed in Croatia.